2021
DOI: 10.1111/ajt.16604
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after simultaneous pancreas–kidney transplantation from donation after circulatory death donors: A UK registry analysis

Abstract: There are concerns that simultaneous pancreas-kidney (SPK) transplants from donation after circulatory death (DCD) donors have a higher risk of graft failure than those from donation after brain death (DBD) donors. A UK registry analysis of SPK transplants between 2005 and 2018 was performed. Pancreas survivals of those receiving organs from DCD or DBD donors were compared. Multivariable analyses were used to adjust for baseline differences between the two groups and to identify factors associated with pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
13
3
Order By: Relevance
“…This was a non-propensity matched, retrospective study, where the authors reported similar 5-year recipient survival rates between DCD and DBD groups (91.5 vs. 89.1%, p = 0.85). Five-year pancreas DCD graft survival was also in line with pancreas DBD graft survival In 2021, a recent UK registry analysis demonstrated on both univariate and multi-variate analysis no statistical difference in 5-year graft or patient survival between DCD and DBD donor groups (13). The authors identified that DCD donors were significantly younger (30 vs. 37, p < 0.01), had a lower rate of stroke (as a cause of death), had lower terminal creatinine and had lower pancreas risk index scores compared to DBD donors.…”
Section: Discussionmentioning
confidence: 74%
“…This was a non-propensity matched, retrospective study, where the authors reported similar 5-year recipient survival rates between DCD and DBD groups (91.5 vs. 89.1%, p = 0.85). Five-year pancreas DCD graft survival was also in line with pancreas DBD graft survival In 2021, a recent UK registry analysis demonstrated on both univariate and multi-variate analysis no statistical difference in 5-year graft or patient survival between DCD and DBD donor groups (13). The authors identified that DCD donors were significantly younger (30 vs. 37, p < 0.01), had a lower rate of stroke (as a cause of death), had lower terminal creatinine and had lower pancreas risk index scores compared to DBD donors.…”
Section: Discussionmentioning
confidence: 74%
“…Registry analysis in the UK and Sweden showed no difference in pancreas allograft survival between SPK recipients from DBD donors and DCD donors [62,63]. In both studies, CIT was shorter for DCD donors.…”
Section: Specificities Related To Donation After Cardiac Deathmentioning
confidence: 77%
“…Others have shown that concerns about the impact of delayed graft function on longer-term graft survival in kidneys from DCD donors are largely unfounded, though periods of delayed graft function of more than 14 days were associated with adverse graft survivals [27]. Contrary to previous work from the US that suggested that donation after circulatory death was a risk factor for diminished pancreas graft survival [28], a recent national registry analysis from the UK, where almost 20% of pancreas transplants are from DCD donors, showed no significant difference between DCD versus DBD five-year risk-adjusted pancreas graft survival [9].…”
Section: Variation In Organ Utilization Between Centresmentioning
confidence: 97%
“…The UK has high rates of organ transplantation from DCD donors [7][8][9], and a relatively old deceased donor population. For example, the median age of donors of transplanted kidneys in the UK is 52 years versus 36 years in the United States (US) [2].…”
Section: Organ Donation and Transplantation In The Ukmentioning
confidence: 99%